Climate change adaptation exertions on the use of alternative water resources in Antalya, Türkiye - Kilinc, Elif Ayyuce; Tanik, Aysegul; Hanedar, Asude; Gorgun, Erdem (Frontiers in Environmental Science, 2023)
This study presents the payback periods of applying rainwater harvesting (RWH) and/or graywater reuse (GWR) systems as alternative water resources in different building typologies, such as a hospital, shopping mall, and hotel. These buildings are under operation in the Antalya Province of Türkiye, which is a large city having the densest tourism activities. The significance of the work performed through the cost-benefit analyses for the selected case studies basically lies on the water savings while serving to four of the sustainable development goals, namely, clean water and sanitation, sustainable cities and communities, responsible consumption and production, and climate action. These efforts may be considered valuable urban-based solutions toward climate change effects. Thorough surveys on the existing selected typologies are conducted regarding their water consumption and probable water savings via reuse activities. As-built plumbing projects and plans are also investigated during the accomplishment of the comprehensive design work leading to the calculation of the total investment and operation costs of the rainwater harvesting and graywater reuse practices. The up-to-date prices are used in monetary terms, and euro currency is used to make the results more meaningful by the interested parties. All the selected typologies undergo cost-benefit analysis for both of the alternative water reuse systems. The payback periods are calculated as 6, 2, and 9 years for RWH and as 5, 6, and 9 years for GWR for the hospital, shopping mall, and the hotel, respectively. The water savings for RWH varied between 20% and 50% whereas for GWR, the range was 48%–99%. Both of the systems are performed for the shopping mall simultaneously, and the resulting payback period is found to be 5 years, and water saving reached 72%. Recent information on the amortization periods in the literature states that less than a decade demonstrates achievable and highly acceptable applications. As such, the design attempts in this study also correlated with these findings. However, feasibility of these practices may be increased by encouraging the public on their utility and benefit of water savings. As is the case in many of the developed countries, incentives like tax reductions and even exemptions may be realized to achieve better applicability of these alternative technologies.